67 B-cell receptor heavy chain repertoire profiling using an augmented transcriptome. (10th December 2020) - Levy, Eric; Milani, Pamela; Bartha, Gabor; Abbott, Charles; Power, Robert; McClory, Rena; Li, Robin; West, John; Lyle, John; Boyle, Sean; Chen, Richard
Abstract : Background: Comprehensive profiling of the tumor and tumor microenvironment (TME) is a critical tool for furthering our understanding of tumor progression and response to treatment, including immunotherapies. To address this challenge, we developed an augmented, immuno-oncology-optimized exome/transcriptome platform, ImmunoID NeXT TM, which provides a more comprehensive view of the tumor and TME from limited FFPE tumor biopsies. We have recently added the ability to profile the B-cell receptor (BCR) heavy chain. Here, we show that ImmunoID NeXT is now able to accurately and reproducibly profile abundant B-cell clones and provide information on the diversity of B-cells in tumor samples. Methods: We analyzed multiple replicates of PBMCs to examine the reproducibility of BCR sequence identification using ImmunoID NeXT. Utilizing a standalone BCR sequencing approach, we further evaluated the concordance of top clones to those identified by ImmunoID NeXT. In addition, we analyzed the reproducibility of BCR sequences in patient-derived FFPE samples. Finally, we used ImmunoID NeXT to profile the B-cell clonal diversity across over 500 solid tumor samples. Results: Reproducibility in PBMC samples was very high, with abundances of clones shared between replicates being very concordant (R 2 >0.92, R 2 >0.86, and R 2 >0.97 for IgG, IgM, and IgA, respectively). When comparing to a standalone BCR sequencing method that profiles IgM and IgG, we observed highly concordant abundances (R 2 >0.72 and R 2 >0.82 in IgM and IgG, respectively), as well as strong overlaps of top clones. When comparing subsequent curls of a tumor FFPE sample, we also achieved a high concordance of clonal abundances (R 2 >0.92, R 2 >0.93, and R 2 >0.76 for IgG, IgM, and IgA, respectively). Finally, we observed differences in clonal diversity of B-cell repertoires across over 500 solid tumor samples. Conclusions: We demonstrate that ImmunoID NeXT can be used to reproducibly, sensitively, and accurately profile high-abundance BCR heavy chain clones, including coverage of all major isotypes. In addition, we show how ImmunoID NeXT can profile the diversity of the BCR repertoire across a variety of tumor samples. Combined with the platform's TCR profiling capabilities, ImmunoID NeXT can provide insight into the diversity of the immune repertoire, contributing to its ability to provide comprehensive analysis of both the tumor and TME from a single FFPE sample.